Sexual Consent Perspektif Maqasid Syariah: Studi Analisis Kritis - Achmad Reza Hutama Al Faruqi; Sayyid Muhammad Indallah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This article aims to explain the law of sexual consent or sexual consent according to maqasid sharia. Lots of approval and attraction to women, molestation, persecution that causes feelings of oppression and speech. Even in the West there is violence, so that Western women demand the freedom of their body rights. From this sexual agreement, feminism aims to seek justice or benefit for them. In compiling this article, the author uses critical analysis methods to explain the concept of feminism and sexual consent. The results of this study conclude that sexual consent according to Westerners is a solution so that no more treatment is recommended. In fact, Muslims also participate and agree to the concept. This is, which is contrary to maqashid shari'ah or the existence of shari'ah. So that consent and acceptance will only cause harm.